Thermochronological record of tectonic events in central and southeastern South China since the Mesozoic - Tao, Ni (Curtin University, 2014)
This study determines the Mesozoic–Cenozoic time-temperature evolution of SE South China, presenting a fully reconstructed thermal history and a critical framework for future research on the Mesozoic–Cenozoic geotectonic evolution of SE South China. This study provides a way to examine how horizontal tectonics led to continental-scale vertical movements and basin formation, and how this may be responsible for a number of enigmatic broad mountain belts and magmatic provinces in the global geological record.